The Adequacy of International Legal Obligations for Environmental Protection During Armed Conflict - Arie Afriansyah (Indonesia Law Review, 2013)
Since it first developed, the law of war has focused on protecting human beings. It prioritises human protection by controlling the conduct of belligerents in order to minimise human injuries and casualties. However, the consequences of war are seldom limited to human casualties. War also causes major destruction to the environment. This article shows that despite prioritising human protection, international law provides a significant number of rules to protect the environment during armed conflicts . Contrary to claims that existing rules are insufficient, the law of war adequately safeguards the environment during armed conflicts by prohibiting certain military activities that may cause significant damage to the environment. Furthermore, there are peacetime regulations that may continue to bind belligerents in times of war.